2017
DOI: 10.1523/jneurosci.1760-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dichoptic Masking in Visual Cortex of Amblyopic Macaque Monkeys

Abstract: In amblyopia, abnormal visual experience leads to an extreme form of eye dominance, in which vision through the nondominant eye is degraded. A key aspect of this disorder is perceptual suppression: the image seen by the stronger eye often dominates during binocular viewing, blocking the image of the weaker eye from reaching awareness. Interocular suppression is the focus of ongoing work aimed at understanding and treating amblyopia, yet its physiological basis remains unknown. We measured binocular interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 24 publications
7
50
0
Order By: Relevance
“…Under conditions of normal binocular viewing (same stimuli in both eyes), this increased masking would result in a suppression of low spatial-frequency information seen through the amblyopic eye. This conclusion in humans with amblyopia gains support from a recent nonhuman primate model of amblyopia in which it has also been shown that there is reduced dichoptic masking by cells driven by the amblyopic eye 25 ; this, in principle, could be due to attenuation (a threshold offset) or reduced contrast gain per se. Shooner et al 25 didn't present their stimuli at a constant suprathreshold contrast as we were able to do psychophysically.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Under conditions of normal binocular viewing (same stimuli in both eyes), this increased masking would result in a suppression of low spatial-frequency information seen through the amblyopic eye. This conclusion in humans with amblyopia gains support from a recent nonhuman primate model of amblyopia in which it has also been shown that there is reduced dichoptic masking by cells driven by the amblyopic eye 25 ; this, in principle, could be due to attenuation (a threshold offset) or reduced contrast gain per se. Shooner et al 25 didn't present their stimuli at a constant suprathreshold contrast as we were able to do psychophysically.…”
Section: Discussionmentioning
confidence: 59%
“…This conclusion in humans with amblyopia gains support from a recent nonhuman primate model of amblyopia in which it has also been shown that there is reduced dichoptic masking by cells driven by the amblyopic eye 25 ; this, in principle, could be due to attenuation (a threshold offset) or reduced contrast gain per se. Shooner et al 25 didn't present their stimuli at a constant suprathreshold contrast as we were able to do psychophysically. Therefore, their result supports the reduced amblyopic-to-fellow eye inhibition but is not definitive about its cause.…”
Section: Discussionmentioning
confidence: 59%
“…Specifically, measurements from the primary visual cortex of non-human primates reared to model amblyopia suggest only a weak shift in neuronal ocular dominance preferences in primary visual cortex -more notable effects include an overall reduction in binocularly responsive neurons, as well as abnormal monocular receptive fields for the weaker eye [38]. Consistent with this observation, physiological measurements in primates suggest that the visual cortex of adult amblyopes is characterized not only by reduced excitatory drive from the weaker eye, but also by active, ongoing interocular suppression of the weaker eye, perhaps reflecting asymmetric gain control [39]. Primate amblyopia models have also revealed changes in tuning and interocular suppression beyond V1 [40].…”
Section: Adult Binocular Vision Can Be Improved Through Long-term Tramentioning
confidence: 74%
“…11 Huang and colleagues 12 also reported that the amblyopic eye's temporal synchrony sensitivity, which is defined as the minimum degree of temporal phase difference that enables participants to discriminate that the target is flickering asynchronously in time, was considerably higher than that of the fellow eye. These visual deficits in spatial and temporal processes are considered to be from some abnormalities in the developed visual system in the brain [13][14][15][16][17][18] rather than those in the eye. Since the problems reside in the neural circuitry rather than anatomy of the eye, they cannot be directly corrected optically.…”
mentioning
confidence: 99%